Middle to Late Miocene Contractional Deformation in Costa Rica Triggered by Plate Geodynamics - Mescua, Jose Francisco (2017)
Contractional deformation in Costa Rica is usually attributed to the subduction of the aseismic Cocos Ridge. In this work, we review the evidences for contraction in the middle to late Miocene, prior to the arrival of the Cocos Ridge at the Middle America Trench. We find that the Miocene phase of contractional deformation is found in all of Costa Rica, probably extending to Nicaragua as well. The widespread distribution of this event requires a regional or plate geodynamic trigger. We analyze the possible mechanisms that could produce the onset of contractional deformation, using the better known case of subduction orogeny, the Andes, as an analog. We propose that a change in the direction of the Cocos plate since ∼19 Ma led to a change from oblique to orthogonal convergence, producing contractional deformation of the upper plate.